Fluorescent labeling of cranberry proanthocyanidins with 5-([4, 6-dichlorotriazin-2-yl]amino)fluorescein (DTAF). (1st January 2015) - Feliciano, Rodrigo P.; Heintz, Joseph A.; Krueger, Christian G.; Vestling, Martha M.; Reed, Jess D.
Highlights: We fluorescently labeled proanthocyanidins from cranberries. Fluorescent proanthocyanidins were characterized by mass spectrometry. We report one and two fluorescent moieties covalently bound to proanthocyanidins. Microscopy showed E. coli agglutination with fluorescent proanthocyanidins. Abstract: A novel methodology was developed to elucidate proanthocyanidins (PAC) interaction with extra-intestinal pathogenic Escherichia coli (ExPEC). PAC inhibit ExPEC invasion of epithelial cells and, therefore, may prevent transient gut colonization, conferring protection against subsequent extra-intestinal infections, such as urinary tract infections. Until now PAC have not been chemically labeled with fluorophores. In this work, cranberry PAC were labeled with 5-([4, 6-dichlorotriazin-2-yl]amino) fluorescein (DTAF), detected by high-performance liquid chromatography with diode-array detection and characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). We report single and double fluorescent-labeled PAC with one or two chlorine atoms displaced from DTAF in alkaline pH via nucleophilic substitution. Fluorescent labeling was confirmed by fragmentation experiments using MALDI-TOF/TOF MS. Fluorescent labeled PAC were able to promote ExPEC agglutination when observed with fluorescence microscopy. DTAF tagged PAC may be used to trace the fate of PAC after they agglutinate ExPEC and follow PAC-ExPEC complexes in cell culture assays.